Soft Computing : Techniques in Engineering Sciences (Volume 1) - Ram, Mangey; Singh, Suraj B.; Ram, Mangey; Singh, Suraj B. (De Gruyter, 2020)
Soft computing is used where a complex problem is not adequately specified for the use of conventional math and computer techniques. Soft computing has numerous real-world applications in domestic, commercial and industrial situations. This book elaborates on the most recent applications in various fields of engineering.
Knowledge Unlatched
English
Keywords: Computer programming / software development; Computers; Software Development & Engineering; General